EventGO / Cassandra Grace Hamarah ... [et al.] - Hamarah, Cassandra Grace; Nazarudin, Nazira Farahin; Victor Luna, Venessa Kumang Amen; Johnny, Cindy (2021)
Planning an event is a stressful and challenging task requiring many hours and days spent researching and calling various vendors to check on availability and pricing. On the other hand, event vendors would often have difficulty reaching their target market as there are potential customers who are not aware of their existence. Due to the current Covid-19 pandemic that hit globally in 2020, many event vendors, especially local vendors, have experienced a severe sustainability issue due to cancellation and lack of business. According to the Bureau of Labor Statistics (2021), the job growth for meetings and event planners is expected to grow at 11%. The EventGO application is an e-commerce platform that acts as an online intermediary between host event management vendors and customers. This one-stop center allows vendors to showcase and sell their services. Simultaneously, it eases customers in planning their events as it has many options to choose from various vendors under one "roof." It features filters for users to choose and find specific services that fit their desired criteria, such as location, pricing, popularity, and ongoing promotions. The application also features a chatting platform that allows users and vendors to communicate and inquire about their services. Furthermore, it provides trending event styles, blogs on recommended services, and a reviews platform according to the users' liking, where they can refer to it and plan their events easily. Not only is EventGo a game-changer in the event industry, but it also helps to make planning for an event a stress-free experience.